Correlation of Iron Deficiency Status with Thyroid Profile among Subclinical and Overt Hypothyroidism Patients Attending a Tertiary Care Hospital in Puducherry, India: A Cross-sectional Study - Angel Mercy Sylus; M. Priyatharshini; P. Muraliswaran; M. Lavanya (Acta Medica International)
Introduction: Hypothyroidism and iron deficiency are both highly prevalent disorders that share certain similar clinical presentations, implying the possibility for their coexistence. Hence, the objectives of this study were to evaluate serum iron indices and thyroid function tests in subclinical and overt hypothyroidism compared to healthy controls and to investigate the relationship between iron indices and thyroid function in subclinical and overt hypothyroidism. Materials and Methods: This hospital-based cross-sectional study included 154 participants, aged between 25–60 years, grouped as 46 subclinical hypothyroid patients, 58 overt hypothyroid patients, and 50 healthy controls. Their serum thyroid function and iron indices, namely ferritin, iron, total iron-binding capacity (TIBC), and transferrin saturation (TSAT), were estimated and compared between the groups. Results: The mean age of participants was 37.76 ± 7.13 years. Serum ferritin, iron, and TSAT were significantly lower, while TIBC was higher, in both the subclinical and overt hypothyroid groups compared to healthy subjects. In subclinical and overt hypothyroidism, thyroid-stimulating hormone showed a significant negative correlation with ferritin, iron, and TSAT, but positively correlated with TIBC. Free thyroxine correlated positively with ferritin, iron, and TSAT in both the hypothyroid groups but correlated negatively with TIBC in overt hypothyroidism only. Free triiodothyronine showed a positive correlation with ferritin in overt hypothyroidism. Conclusion: The study results suggest that iron deficiency correlates with thyroid function in both subclinical and overt hypothyroidism, demonstrated by decline in ferritin, iron, and TSAT with an increase in TIBC. It implies the likely coexistence of iron deficiency with subclinical and overt hypothyroidism and emphasizes the necessity for early assessment of iron status in patients with thyroid hypofunction to ensure appropriate management.